The Game of Innovation. Is Gamification a New Trendsetter? - Roxana Procopie; Robert Bumbac; Smaranda Giușcă; Andra Vasilcovschi (Amfiteatru Economic Journal, 2015)
With the evolution of information technology and that of the Internet, society has changed and so did the needs of Generation Y that aims to be more involved in decision making processes and have an overall open and positive approach to innovation. This article aims to analyse the contribution of adopting techniques and methods specific to gamification to the results of the innovation process from Generation Y's perspective. The chosen research method is that of quantitative research, resorting to conducting a statistical survey in order to identify the major changes in Generation Y and of the specific way it acts and interacts. The focus is particularly on the implications that this phenomenon has on the innovation process. The Millennials want to be in control of their lives and take active part in processes that involve them. Gamification is one of the modern tools that facilitates this, it promotes communication between organizations, public or private, and individuals and benefits innovation.
Keywords: O30; M10; 330; innovation; gamification; Generation Y